Underestimated sources of flavonoids, limonoids and dietary fiber: Availability in orange's by-products. (January 2015) - Russo, Marina; Bonaccorsi, Ivana; Inferrera, Veronica; Dugo, Paola; Mondello, Luigi
Highlights: Nutraceuticals were determined in orange juice and in all the corresponding by-products. The major classes of compounds were: flavanones, flavones and phenolic acids. The analyses were conducted by HPLC/PDA/MS with ESI (negative) and APCI (positive). Hesperidin was purified by preparative LC-LC/PDA/MS. Significant amounts of dietary fiber could be recovered from industrial orange solid (peels and pulps) wastes. Abstract: This study reports a comprehensive investigation on the presence of flavonoids, limonoids and dietary fiber determined by HPLC in all the by-products of the industrial transformation of orange. Seeds were the richest source of bioactive molecules, with flavanones being the most abundant, followed by phenolic acids (238 mg/kg). However, p-hydroxybenzoic acid and caffeic acid were highly represented also in the exhausted peels and pulps (560 mg/kg). Limonoids were determined exclusively in seeds. Among all the by-products it was found that waste water is extremely rich of hesperidin (19, 500 mg/kg). For this reason an only eco-friendly preparative HPLC method for the recovery and purification of hesperidin from waste water was developed. Dietary fiber was determined in exhausted peels and pulps which resulted to be rich sources of insoluble dietary fiber. The results show that the by-products here investigated represent important sources of nutraceuticals as ingredients useful for functional food preparations.